(untitled) (Revista de Ciências Agroveterinárias, 2015)
Many species of the genus Physalis are gaining prominence for its numerous medicinal and nutraceutical properties. Among the species of this genus, Physalis peruviana, P. pubescens and P. angulata, stand out, being easy to grow, having characteristic flavor, and beneficial health properties. Insufficient knowledge about the needs and optimal conditions for its cultivation, being fundamental in morpho-anatomy study that can better facilitate the distinction among species. The objective was to analyze morpho-anatomically the P. peruviana, P. pubescens and P. angulata stems, seeking characteristics that can help in distinguishing species and analyzing their structures to diagnose a possible adaptive favorable condition for the species in Western Paraná State. Plants of the three species were grown in a protected environment in Marechal Cândido Rondon, PR, Brazil. When they reached the reproductive stage, stems were sectioned, placed in blocks, and analyzed, according to techniques described in the literature. The results showed that P. peruviana, P. pubescens and P. angulata share many morphological and anatomical features in their stems and presented some distinct anatomical features. The species have mesomorphyc characteristics and adaptive structures to elevated temperatures and herbivory combat, such as a high number of trichomes. Glandular trichomes that can store the active compounds of Physalis were found in the stem. Characteristics found in species of Physalis refer to invasive plants, along the adaptive structures mentioned above, that can encourage commercial cultivation of Physalis in Western Paraná, Brazil.